Cardiac Paraganglioma: Multimodality Imaging of a Rare Tumor - Patrianakos, Alexandros P. (JACC Case Rep, 2021)
Paragangliomas are rare tumors of chromaffin cells arising from an extra-adrenal location. Unlike pheochromocytomas, they are seldom functional. We present a case of pericardial paraganglioma incidentally encountered on an echocardiographic study, focusing on the characteristic features the tumor demonstrates on different imaging modalities. (Level of Difficulty: Intermediate.)